The Role of Content Creators Through Social Media at CV Demora Indonesia Jakarta - Setiawan, Elfa; Permatasari, Dhea (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to determine the role of content creators through social media at CV Demora Indonesia, Jakarta to determine what activities are carried out by content creators to increase sales, and to determine what solutions are taken to deal with obstacles that occur. This observation and research focus on the problem of teamwork in the company which is still very lacking so that it has an impact on marketing strategies that are less than optimal and less effective to implement. The data collection method is taken from direct observation and interviews with informants. Based on the results of observations, it can be concluded that the role of content creators in digital marketing strategies is quite important for creating various advertisements or promotions to increase sales and teamwork is also very important to achieve common goals